The rewarding nature of social interactions - Krach, Sören; Paulus, Frieder M.; Bodden, Maren; Kircher, TIlo (Frontiers in Behavioral Neuroscience, 2010)
The objective of this short review is to highlight rewarding aspects of social interactions for humans and discuss their neural basis. Thereby we report recent research findings to illustrate how social stimuli in general are processed in the reward system and highlight the role of Theory of Mind (ToM) as one mediating process for experiencing social reward during social interactions. In conclusion we discuss clinical implications for psychiatry and psychotherapy.